The Comparison of E-Modules and Print Modules to See Character Like to Read on Elementary School Students - Syahrial, Syahrial; Asrial, Asrial; Kurniawan, Dwi Agus; Luthfiah, Qonita (Journal of Education Technology, 2021)
Technological advances are not new for students in Indonesia, whether they use electronic learning media in their daily lives or not. One example is the application of electronic modules. This study aims to determine the comparison of the print modules and the e-modules. This type of research is comparative research. Comparative research is research that compares the object under study. The method used in this study is a quantitative method using a survey research design. The sample of this research is class IV students, totaling 22 people. Data analysis used descriptive and inferential statistics, namely analyzing data by describing the data that has been collected. The results of this study were from the two teaching materials applied, namely the printed module and the electronic module, it was possible to see indicators of reading fondness characters. In the study, the dominant results were good for looking at indicators of reading fondness characters with the application of electronic modules, while for the application of print modules in the sufficient category, it can be seen that there are differences between the two teaching materials that are applied to see indicators of reading fondness characters, this is reinforced by the test results t that has been done, where the obtained sig is smaller than 0.05 then there is a difference between the two. So the electronic module based on local wisdom needs to be applied by teachers to instill the character of reading fondness among students.